Comparative efficacy of different weight loss treatments on knee osteoarthritis: A network meta‐analysis - Panunzi, Simona; Maltese, Sabina; De Gaetano, Andrea; Capristo, Esmeralda; Bornstein, Stefan R.; Mingrone, Geltrude (Obesity reviews, 2021)
Summary The lifetime risk of developing symptomatic knee osteoarthritis is 60% in subjects with obesity. It is unclear which is the best weight loss interventions leading to a meaningful improvement of osteoarthritis symptoms and clinical conditions in subjects with obesity. Our network meta‐analysis compares different weight loss interventions on the improvement of osteoarthritis symptoms and clinical conditions in subjects affected by obesity. PubMed, Embase, and Cochrane databases were systematically searched for eligible studies until November 2020. Thirty eligible studies comprising 4651 adults (74.6% women) were included. The most effective interventions reducing pain were bariatric surgery, low‐calorie diet and exercise, and intensive weight loss and exercise (−62.7 [95% CrI: −74.6, −50.6]; −34.4 [95% CrI: −48.1, −19.5]; −27.1 [95% CrI: −40.4, −13.6] respectively). For every 1% weight loss Western Ontario and McMaster Universities Osteoarthritis (WOMAC) pain, function, and stiffness scores decreased by about 2% points. In conclusion, our meta‐analysis shows that a substantial weight loss is necessary to reduce significantly knee pain and joint stiffness and to improve physical function: 25% weight reduction from baseline is necessary to obtain a 50% reduction of each subscale of the WOMAC score. However, performing physical exercise is essential to preserve the lean body mass and to avoid sarcopenia. Our results apply to a large spectrum of body mass index (BMI), from overweight to severe obesity.